23 years of the discovery of Helicobacter pylori: Is the debate over? - Ahmed Niyaz (BMC, 2005)
Abstract The Gram negative curved bacillus H. pylori has become the prize bug of all times. Barry Marshall and Robin Warren the two discoverers of this organism have been awarded with this year's Nobel Prize. The Nobel committee at the Karolinska Institute of Sweden has selected this paradigm shift discovery of 1982 as the most impacting in medical sciences. This award has surprised many as the Nobel assembly has selected this 'Robert Koch styled medical detective work' for the prize as compared to many outstanding basic research stories on the waitlist. This editorial briefly touches the significant impact of H. pylori on gastroduodenal management and the path forward as the bug has become quite controversial in recent times.